Analisis Escherichia coli dalam Air Minum Isi Ulang pada Depot Air Minum (DAM) di Wilayah Kerja Puskesmas Kuta Alam Banda Aceh - Aris Winandar; Riski Muhammad; Irmansyah Irmansyah (Universitas Serambi Mekkah, 2020)
Based on preliminary survey results, from 24 refill drinking water depots in the working area of Kuta Alam Health Center in Banda Aceh City that have been examined using the relatively simple H2S method by the Kuta Alam Health Center in 2020 in the May period there was no E. coli found. But in the next period the researchers continued the examination of refill drinking water using a different method, the Most Probable Number (MPN). Changes in weather related to rainfall that have an impact on the flow and concentration of ground water are also some of the factors that allow contamination of raw water used by DAMIU in the work area of the Kuta Alam Health Center in Banda Aceh City. The purpose of this study was to determine the quality of drinking water in DAM in the work area of the Kuta Alam Health Center in Banda Aceh. The population in this study were all refill drinking water depots in the working area of Kuta Alam Puskesmas in the city of Banda Aceh, totaling 22 DAMIU. The sample in this study was 50% of the total refill drinking water depots in the work area of the Kuta Alam Health Center in Banda Aceh city of 11 DAMIU. Refillable drinking water that contains positive Escherichia coli from 11 samples studied there are 4 samples that are equal to 36%, and negative ones containing Escherichia coli are as many as 7 samples that are equal to 64%.Keyword: Raw water source, facility maintenance, Eschericia coli in drinking water